2022
DOI: 10.5194/cp-18-1797-2022
|View full text |Cite
|
Sign up to set email alerts
|

Bottom water oxygenation changes in the southwestern Indian Ocean as an indicator for enhanced respired carbon storage since the last glacial inception

Abstract: Abstract. We present downcore records of redox-sensitive authigenic uranium (U) and manganese (Mn) concentrations based on five marine sediment cores spanning a meridional transect encompassing the Subantarctic and Antarctic zones in the southwestern Indian Ocean covering the last glacial cycle. These records signal lower bottom water oxygenation during glacial climate intervals and generally higher oxygenation during warm periods, consistent with climate-related changes in deep-ocean remineralized carbon stor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 124 publications
4
9
0
Order By: Relevance
“…Higher dust deposition in the southern Pacific and the southern Atlantic at 70 ka is consistent with available palaeo-proxy records (Martínez-García et al, 2011;Lambert et al, 2012;Lamy et al, 2014;Thöle et al, 2019). At the same time, palaeoceanographic records from the AZ suggest a decrease in EP during MIS4 (Anderson et al, 2009;Jaccard et al, 2013;Studer et al, 2015;Thöle et al, 2019;Amsler et al, 2022;Weber et al, 2022).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Higher dust deposition in the southern Pacific and the southern Atlantic at 70 ka is consistent with available palaeo-proxy records (Martínez-García et al, 2011;Lambert et al, 2012;Lamy et al, 2014;Thöle et al, 2019). At the same time, palaeoceanographic records from the AZ suggest a decrease in EP during MIS4 (Anderson et al, 2009;Jaccard et al, 2013;Studer et al, 2015;Thöle et al, 2019;Amsler et al, 2022;Weber et al, 2022).…”
Section: Discussionsupporting
confidence: 83%
“…Alkenone fluxes (Lamy et al, 2014;Martínez-García et al, 2014), as well as opal and organic carbon fluxes (Thöle et al, 2019;Amsler et al, 2022), reconstructed from sub-Antarctic sediment cores suggest that EP was higher in the SAZ during MIS4 than present-day levels. In addition, bottom water oxygenation records indicate a deep-ocean oxygenation decrease during MIS4, which might suggest increased respired carbon storage in the deep ocean (Amsler et al, 2022) but could also reflect a change in ocean dynamics and water residence time. It has been suggested that the sub-Antarctic EP increase during MIS4 was due to higher iron fluxes into the Southern Ocean.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The simulated increase in diatom abundance east of New Zealand, due to deeper MLD in experiments FW and FWFE, is in agreement with brassicasterol concentrations (a marker for diatoms) (Figures 5a-5g) observed in the Chatham rise core (Sachs & Anderson, 2005). Increased diatom abundance south of ∼50°S in the Atlantic in FW and FWFE and a decrease in diatoms between ∼50°S and ∼55°S in the Indian sector in FE and FWFE, are also in agreement with the marine sediment opal flux records from the Southern Ocean (Amsler et al, 2022;Anderson et al, 2009;Thöle et al, 2019). In the sub-Antarctic, simulated diatom changes north of ∼50°S in FW are consistent with the proxy records from Atlantic (Anderson et al, 2014;Sachs & Anderson, 2003) and Indian sectors (Amsler et al, 2022;Thöle et al, 2019), while in the FE and FWFE simulations, the diatom increase is consistent with only one record (Amsler et al, 2022) in the Indian sector.…”
Section: Paleoceanography and Paleoclimatologysupporting
confidence: 88%
“…(c,f,i) EP anomalies at 177.5 m (gC m −2 yr −1 ). Paleo‐proxy estimated anomalies at 39ka compared to 40ka are added on top of the simulated anomalies for qualitative comparison of model and data: (a, d, g) opal flux (triangles) (Amsler et al., 2022; Anderson et al., 2009; Thöle et al., 2019) and brassicasterol concentration (circle) (Sachs & Anderson, 2005); (c, f, i) alkenone flux (diamonds) (Sachs & Anderson, 2003, 2005) and organic carbon flux (square) (Anderson et al., 2014; Thöle et al., 2019). Dark (light) orange represents significantly (slightly) higher values, while dark (light) blue represents significantly (slightly) lower values.…”
Section: Resultsmentioning
confidence: 99%